Kultur Embrio Kelapa Kopyor Menggunakan Beberapa Konsentrasi BA Dan Air Kelapa - Marveldani; Desi Maulida; Lisa Erfa (Politeknik Negeri Lampung., 2020)
Coconut Kopyor is an abnormal fruit, the ordinary coconut flesh is attached to the shell and separated from coconut water while Coconut Kopyor, fruit flesh is not attached to the shell but is mixed with coconut water. Kopyor coconut cannot be used as a seed (seed). The growth of kopyor coconut embryos can only be done in a laboratory with embryo culture technology. Embryo culture is the only way to produce true to type coconut kopyor seeds that can produce 80% kopyor coconut in one kopyor coconut plant, kopyor coconut seedlings produced can support government programs in increasing the productivity of kopyor coconut through the provision of quality seeds. Research on kopyor coconut embryo culture was carried out at the Laboratory of Tissue Culture at Lampung State Polytechnic. The experiment was carried out using a RAL, with 15 treatment combinations of BA media formulations (0, 2, and 4) with coconut water (0 ml / l, 100, 150, 200, 250 ml / l). The observed variables were the percentage of embryos sprouting, when the shoot appeared, shoot height, number of roots, and number of leaves. The results showed that the use of BA 4 mg / l without the addition of coconut water increased the percentage of sprouts, faster time for shoots, and highest shoot height.